Rec. [Ofélia Paiva Monteiro (2018). Variações sobre temas camonianos. Coimbra: CIEC]. - Marnoto, Rita (2020)
(2020). Rec. [Ofélia Paiva Monteiro (2018). Variações sobre temas camonianos. Coimbra: CIEC]. Colóquio. Letras, 221, 276-278. ISSN 0010 1451